Polarization without radicalization: political radicalism in Albania in a comparative perspective (2016)
ABSTRACT: Since the collapse of communism, political radicalism has been an important part of the political scene in Europe. The 2008 financial crisis furthered this trend, giving rise to new waves of radicalization. Albania appears to be a curious exception to this trend. Unlike most other countries in Eastern Europe, there have been no successful radical parties in Albania since the collapse of communism in 1991. In the same fashion, social protests in Albania in recent years have been fleeting and far less radical than other protest movements in other countries in the region (Bulgaria, Greece and Turkey). This article argues that the relative lack of political radicalization in Albania is due to its traumatic communist past combined with a high level of bipolarization. The bitter experience with national–communism reduced the attractiveness of both far right and far left discourses in Albania. The high levels of political bipolarization, on the other hand, divided the Albanian political sphere into two antagonistic camps. Such a deep division subsumed other possible cleavages.